SUPPLY OPTIMIZATION OF OBJECTS AND NATURAL TOURIST ATTRACTIONS IN SITU GUNUNG, GUNUNG GEDE PANGRANGO NATIONAL PARK - Icha Agustina; Sambas Basuni (Media Konservasi, 2021)
Situ Gunung Natural Tourism area as part of Gunung Gede Pangrango Natural Park utilization zone is a popular natural tourism destination. Therefore, the assessment on objects and attraction natural tourism attraction of Situ Gunung (ODTWASG) based on the satisfaction of management as the supply and visitors as the demand is essential to identify object and nature attraction that ecologically, socially, and economically need to be improved or maintained by the managers. The assessment results data were then processed and analyzed by using conformity scale method and Importance Performance Analysis (IPA). The results showed that there was one unsatisfying attribute on both parties in economic scale, i.e., the making of suspension bridge. Besides, there were two attributes of economic ODTWASG that have not been managed optimally. Thus, it has not contributed to customer satisfaction, which were food and beverages prices at the food court as well as water tourism object entrance fee. Therefore, ODTWASG supply optimization could focus on these two economic attributes; first, setting and adjusting the attribute of food and beverages prices, and second, improving water tourism quality. Key words: Importance Performance Analysis (IPA), satisfaction, supply and demand